Influência das áreas verdes sobre o conforto térmico urbano: estudo de caso em Passo Fundo/RS - Giacomelli, Bruna (2021)
The city should prioritize its development in a way that would provide a link between the built environment and the natural environment, promoting balanced relationships between man and green areas. However, due to the excessive increase in population and the intense use and occupation of urban land without adequate planning, the densification and waterproofing of urban centers provided a decrease in thermal comfort in cities. Changing the microclimate of central areas can lead to the Ilha de Calor phenomenon and further impair the thermal comfort and health of residents. This effect can be mitigated with strategies to implement vegetation, materials and typologies. Thus, the work presented the influence of green areas on urban thermal comfort in a central area of the city of Passo Fundo/RS in order to verify the thermal conditions of the environment. From the collection of data, such as temperature, relative air humidity, morphological characteristics and existing vegetation, it was possible to analyze the correlation of these factors with the Temperature and Humidity Index (ITU) or Effective Temperature (ET) and the Thom Discomfort Index (RTD). The results indicated a significant difference between the central area and the INMET station located in an open area, outside the urban perimeter, proving the existence of Urban Heat Island in the study area. Among the points collected in the city center, no significant difference in temperature was detected, regardless of the characteristics analyzed in the surroundings. This reinforces, in relation to thermal comfort, the need to use more indicators to obtain more reliable results for application in similar research.